2020
DOI: 10.1002/brb3.1523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the contribution of COMT gene Val158/108Met polymorphism (rs4680) to working memory training‐related prefrontal plasticity

Abstract: Background: Genetic factors have been suggested to affect the efficacy of working memory training. However, few studies have attempted to identify the relevant genes. Methods:In this study, we first performed a randomized controlled trial (RCT) to identify brain regions that were specifically affected by working memory training.Sixty undergraduate students were randomly assigned to either the adaptive training group (N = 30) or the active control group (N = 30). Both groups were trained for 20 sessions during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…In our study, we were only able to find a training gain for verbal learning in the naMCI LMX1A-AA group 1-month after WM training. Lastly, similar to our study, carriers of the val allele of the COMT Val 158 Met polymorphism, another gene that regulates the dopaminergic system, also showed lower baseline performance but greater plasticity of working memory ( Bellander et al, 2015 ), and showed greater WM training-related prefrontal plasticity ( Zhao et al, 2020 ). Future studies should include the evaluation of COMT polymorphism.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we were only able to find a training gain for verbal learning in the naMCI LMX1A-AA group 1-month after WM training. Lastly, similar to our study, carriers of the val allele of the COMT Val 158 Met polymorphism, another gene that regulates the dopaminergic system, also showed lower baseline performance but greater plasticity of working memory ( Bellander et al, 2015 ), and showed greater WM training-related prefrontal plasticity ( Zhao et al, 2020 ). Future studies should include the evaluation of COMT polymorphism.…”
Section: Discussionsupporting
confidence: 86%
“…The second problem is that genetic studies with cognitive interventions have all looked at only a few candidate genes or DNA markers (e.g., refs. 18 21 ). General cognition is a complex polygenic trait, influenced by thousands of genetic regions, so those past studies cannot give us a full and reliable genetic picture.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that prefrontal cortex dopaminergic synaptic plasticity associated with WMT is significantly influenced by COMT polymorphisms, particularly in older adults. Similarly, in the fMRI study by Zhao and collegues, WMT led to significantly reduced activation in the left prefrontal cortex, but especially for the Met (hetero – and homozygous) versus Val allele carriers, in that neural activation in the left prefrontal cortex of Val/Val carriers was unaltered between pre- and post-training ( 65 ). Conversely, the tDCS study examining the influence of COMT showed that those with the val/val COMT genotype gained most from 1.5 mA tDCS during visual WMT and from 1 mA tDCS during spatial WMT.…”
Section: Resultsmentioning
confidence: 77%
“…The authors’ concluded that variations in COMT val158met may predict the nature of WM improvement after initial and longitudinal tDCS. It is important to note that in the previous fMRI study that examined the contribution of COMT polymorphisms to WMT-related neuroplasticity, it was conversely found that neural activation in the val/val polymorphism group was least influenced by training ( 65 ). The discrepancy between the two studies could be due to the differences associated with encouraging neuroplasticity effects via WMT, versus brief neurostimulation via tDCS.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation